Big hits on the small screen: an evaluation of concussion-related videos on YouTube. Issue 2 (27th February 2013) - Williams, David; Sullivan, S John; Schneiders, Anthony G; Ahmed, Osman Hassan; Lee, Hopin; Balasundaram, Arun Prasad; McCrory, Paul R
Abstract : Background: YouTube is one of the largest social networking websites, allowing users to upload and view video content that provides entertainment and conveys many messages, including those related to health conditions, such as concussion. However, little is known about the content of videos relating to concussion. Objective: To identify and classify the content of concussion-related videos available on YouTube. Study design: An observational study using content analysis. Methods: YouTube's video database was systematically searched using 10 search terms selected from MeSH and Google Adwords. The 100 videos with the largest view counts were chosen from the identified videos. These videos and their accompanying text were analysed for purpose, source and description of content by a panel of assessors who classified them into data-driven thematic categories. Results: 434 videos met the inclusion criteria and the 100 videos with the largest view counts were chosen. The most common categories of the videos were the depiction of a sporting injury (37%) and news reports (25%). News and media organisations were the predominant source (51%) of concussion-related videos on YouTube, with very few being uploaded by professional or academic organisations. The median number of views per video was 26 191. Conclusions: Although a wide range of concussion-related videos were identified, there is a need for healthcare and educational organisations to explore YouTube as a medium for the dissemination of quality-controlled information on sports concussion.